Community-Based and Crisis Communication Approach to Managing Limited-Escalation Student Protests: Evidence from a Case Study in Yogyakarta - Idham Mahdi; Muhammad Syamsuddin; Sunarso; Suranto (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study aims to analyze the implementation of a community-based approach in managing student demonstrations that experienced limited escalation in Yogyakarta and to evaluate its effectiveness in reducing the potential for conflict. The study employs a qualitative approach using a case study design focused on the demonstration that took place in front of the Yogyakarta Regional Police Headquarters in February 2026. Data were collected through media documentation, digital observation, and literature review, and were analyzed using the Miles, Huberman, and Saldaña interactive model. The results indicate that the community-based approach was implemented through non-repressive strategies, such as the avoidance of excessive force and the selective handling of three students who were handed over to university authorities. This approach proved capable of keeping the situation under control without triggering a broader escalation of conflict. Furthermore, community involvement through the local practice of neighborhood watch played a crucial role in promoting de-escalation of the situation through community-based social control mechanisms. Theoretically, these findings reinforce the concepts of community policing and crisis communication by emphasizing the importance of collaboration, trust, and adaptive communication. The novelty of this research lies in the identification of neighborhood watch as a local form of the community approach, demonstrating that conflict management must be contextualized within the social and cultural practices of the community.